From youth team to first team: An investigation into the transition experiences of young professional athletes in soccer - Morris, R.; Tod, D.; Eubank, M. (International Journal of Sport and Exercise Psychology, 2017)
Using Wylleman and Lavallee [(2004). A developmental perspective on transitions faced by athletes. In M. Weiss (Ed.), Developmental sport psychology (pp. 507-527). Morgantown, WV: Fitness Information Technology] and Stambulova [(2003). Symptoms of a Crisis-transition: A Grounded Theory Study. In N. Hassmen (ed.), Svensk Idrottspykologisk Förening (pp. 97-109). Örebro, Sweden: Örebro University Press] models of transition as conceptual frameworks for the current study, we aimed to explore United Kingdom professional soccer players` (N = 5) experiences going through a youth-to-senior career transition to first team level, and assess the immediate changes that occur during the move. Few studies have assessed this process, and no studies have focused on assessing the changes that may occur between pre- and post-transition. Data collection lasted one month with players interviewed twice, two weeks before, and two weeks after their transition to the first team. Data were abductively thematically content analysed. Prior to transition, players reported high motivation to be successful, but also feeling anxious about the transition to senior sport. Post-transition, players felt more confident about their ability to succeed in senior sport and maintained high levels of motivation to succeed. Family, friends, coaches, and teammates provided emotional, technical, and tangible support to the players throughout the transition, but were also sources of stress for athletes moving to senior sport. These findings suggest ways to assist transitioning athletes, such as the use of buddy systems with senior players.